Combined impact of Lorentz force, micro-rotation, and thermo-migration of particles: Dynamics of micropolar fluids experiencing nonlinear thermal radiation and activation energy - Xiu, Weirong; Salawu, S.O.; Oludoun, O.Y.; Ogunlaran, O.M.; Disu, A.B. (Journal of magnetism and magnetic materials, 2023)
The functional qualities of magneto-micropolar fluid with tiny particles allow for increased lubricating oil usage, increased industrial output, and the development of nanotechnology. However, in such a situation, little or nothing is known about the significance of Lorentz force associated with the behaviour of conducting fluids in magnetic fields, micro-rotation, and thermo-migration of particles as applicable to the control of liquid metals or plasmas. This study focuses on the combined impact of Lorentz force, micro-rotation, and thermo-migration of particles on the dynamics of micropolar fluids experiencing nonlinear thermal radiation and Arrhenius chemical reaction associated with the activation energy. The reactive non-Newtonian, magneto-micropolar nanoparticle fluid flows over a configured two-dimensional stretchy vertical plate. The flow is influenced by activation energy, Brownian movement of tiny particles, thermo-migration of particles and nonlinear thermal radiation. By means of suitable similarity quantities, the partial differential equations governing the flow equations are reduced to ordinary differential equations, and solved numerically using Fehlberg integrating Runge–Kutta scheme. It is worth concluding that the Lorentz force, micro-rotation, and thermo-migration of particles strongly affects the dynamics of micropolar fluids near the wall. A tiny number of particle spins produced by collisions with the boundary dominate the micro-rotation field. •Thermal radiation of reactive magneto-micropolar fluid conveying tiny particles subject to the activation energy.•Parameter sensitivities study of the tiny magneto-micropolar fluid particles for thermal system advancement.•Parameters that the enhances internal heat must be monitored to prevent chemical reaction nanofluid blowup.•A tiny number of particle spins produced by collisions with the boundary dominate the micro-rotation field.•The Lorentz force, micro-rotation, andthermo-migration of particles strongly affects the dynamics of micropolar fluids near the wall.